MODEL PELATIHAN DARING MASIF DAN TERBUKA GURU IPA MADRASAH - Adon Nasrullah Jamaludin; Nanang Suparman (Balai Diklat Keagamaan Bandung, 2021)
This research aims to improve the competence and scientific literacy of madrasah Tsanawiah and Aliyah teachers through MOOC. The Research and Development approach was carried out in training class using Software Tracker phase 1, Physics lesson. The data were collected through classroom participatory observation, interviews, and questionnaires. The subjects were online training participants consisting of madrasah teachers throughout West Java. The result shows that the achievements increased competence and scientific literacy with a very good score of 94,60% and the value of program activities 81%. This study concludes that the training can improve the competence and scientific literacy of teachers and other educational personnel, yet the completeness in all training sessions is still very low (12%). It is suggested that the training should highlight the period by considering materials and characteristic of the participants. Keywords: Literacy; Madrasah Science Teachers; Massive and Open Online Learning; Competence